Underwater soundscape in Seaview Bay, Antarctica, and triple ascending trill of the leopard seal (Hydrurga leptonyx) underwater vocalizations - Dong‐Gyun Han; Jee Woong Choi; Jong‐U Kim; Jeong‐Hoon Kim; Hyoung Sul La (Ecology and Evolution, 2024)
Abstract The underwater soundscape was recorded in Seaview Bay off Inexpressible Island, Ross Sea region Marine protected area, for 3 days in December 2021. Leopard seal Hydrurga leptonyx vocalizations were a prominent sound source that led to variations in ambient sound pressure levels in a frequency range of approximately 150–4500 Hz. Among the 14 call types previously identified, except ultrasound vocalizations, six types of broadcast calls were classified, and their acoustic characteristics were analyzed. We focused on the acoustic characteristics of four low‐frequency calls, clustered in a relatively narrow bandwidth, which have been relatively less studied. We identified a new call type of a triple ascending trill consisting of three trill parts, expanding upon the findings of previous studies. The audio data extracted from leopard seal vocalization videos, recorded by a monitoring camera on sea ice, enhanced the reliability of identifications of the underwater triple ascending trill. We present the unique results of underwater passive acoustic monitoring conducted at Seaview Bay, designated as Antarctic Specially Protected Area No 178. Our results could contribute to the development of detection and localization algorithms for leopard seal vocalizations and can be used as fundamental data for studies related to the vocalization and behavior of this species.